Versatile Cu-II metal-organic framework exhibiting high gas storage capacity with selectivity for CO2: conversion of CO2 to cyclic carbonate and other catalytic abilities - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Sen Gupta, Sayam; Bharadwaj, Parimal K. (Chemistry-A European Journal, 2016)
A linear tetracarboxylic acid ligand, H4L, with a pendent amine moiety solvothermally forms two isostructural metal-organic frameworks (MOFs) L-M (M=Zn-II, Cu-II). Framework L-Cu can also be obtained from L-Zn by post- synthetic metathesis without losing crystallinity. Compared with L-Zn, the L-Cu framework exhibits high thermal stability and allows removal of guest solvent and metal-bound water molecules to afford the highly porous, L-Cu. At 77K, L-Cu absorbs 2.57wt% of H-2 at 1bar, which increases significantly to 4.67wt% at 36bar. The framework absorbs substantially high amounts of methane (238.38cm(3)g(-1), 17.03wt%) at 303K and 60bar. The CH4 absorption at 303K gives a total volumetric capacity of 166cm(3)(STP)cm(-3) at 35bar (223.25cm(3)g(-1), 15.95wt%). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0wt% of CO2 to be absorbed at 1bar and 273K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, L-Cu shows pronounced selectivity for CO2 absorption over CH4, N-2, and H-2 at 273K. The absorbed CO2 can be converted to value-added cyclic carbonates under relatively mild reaction conditions (20bar, 120 degrees C). Finally, L-Cu is found to be an excellent heterogeneous catalyst in regioselective 1,3-dipolar cycloaddition reactions (click reactions) and provides an efficient, economic route for the one-pot synthesis of structurally divergent propargylamines through three-component coupling of alkynes, amines, and aldehydes.
Keywords: click reactions; CO2 absorption; cyclic carbonate; heterogeneous catalysis; metal-organic frameworks